2009
DOI: 10.5055/ajdm.2009.0004
|View full text |Cite
|
Sign up to set email alerts
|

Emergency drills and exercises in healthcare organizations: Assessment of pediatric population involvement using after-action reports

Abstract: Background: Although the Joint Commission on Accreditation of Healthcare Organizations (JCAHO) requires healthcare organizations to demonstrate disaster preparedness through the use of disaster exercises, the evaluation of pediatric preparations is often lacking. Our investigation identified, described, and assessed pediatric victim involvement in healthcare organizations’ disaster drills and exercises using data from after-action reports.Methods: Following the IRB approval, the authors reviewed the after-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…14Y16 However, deficiencies are known to exist in the realm of pediatric disaster preparedness. 17,18 Very few studies have been performed on disaster drills involving children. During pediatric disaster drills, each patient is likely to be accompanied by one or more family members.…”
Section: Discussionmentioning
confidence: 99%
“…14Y16 However, deficiencies are known to exist in the realm of pediatric disaster preparedness. 17,18 Very few studies have been performed on disaster drills involving children. During pediatric disaster drills, each patient is likely to be accompanied by one or more family members.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is expensive and not reported widely to other countries except of Asia. Realistic disaster drills proved to be the most effective technique for enhancing preparedness in Korea because actual hospital disasters rarely occur 27-29…”
Section: Discussionmentioning
confidence: 99%
“…Data suggests that most hospitals perform their disaster drills without pediatric patients. To be prepared for a pediatric surge, children should be included in upcoming simulations (Ferrer et al 2009). It is therefore suggested that the proportion of pediatric patients during such drills be 15-20%.…”
Section: Materials and Staff Requirementsmentioning
confidence: 99%